Comparative Efficacy and Safety of Nivolumab and Nivolumab Plus Ipilimumab in Advanced Cancer: A Systematic Review and Meta-Analysis - Yang, Yi; Jin, Gang; Pang, Yao; Huang, Yijie; Wang, Wenhao; Zhang, Hongyi; Tuo, Guangxin; Wu, Peng; Wang, Zequan; Zhu, Zijiang (Frontiers in Pharmacology, 2020)
Abstract Background: Combination therapy with immune checkpoint inhibitors (ICIs) has been applied in the clinic to achieve synergistic effects and to improve clinical efficacy. Compared with monotherapy, combination therapy seems to have promising efficacy against different advanced cancers. To further verify the effectiveness of combination therapy, we conducted a meta-analysis of the efficacy and safety of nivolumab (NIVO) and NIVO plus ipilimumab (IPI) in advanced cancer. Methods: Electronic databases (PubMed, EMbase, and The Cochrane Library) were systematically searched for applicable studies published in English between January 1990 and June 2019. Relevant outcomes included objective response rate (ORR), disease control rate (DCR), median progression-free survival (mPFS), median overall survival (mOS), and Grade 3–4 adverse events (AEs). Results A total of 1297 patients from 6 studies were included. Compared with NIVO alone, NIVO + IPI is better for advanced tumors. Pooled outcome values were ORR: 1.73 (95% CI: 1.35–2.23), DCR: 1.79 (95% CI: 1.18–2.72), mPFS: 0.22 (95% CI: 0.03–0.41) and mOS: 0.03 (95% CI: −0.20–0.26), Grade 3–4 AEs: 3.58 (95% CI: 2.81–4.55). Conclusion NIVO + IPI is better than NIVO alone for the treatment of advanced cancer, and can significantly improve ORR and DCR and prolong mPFS. Owing to the limited quality and quantity of included studies, more high-quality studies are needed to validate the above conclusions.